Introducing human 3D skin models as a new serological diagnostic tool for severe autoimmune bullous diseases - Huth, Laura; Heise, Ruth; Marquardt, Yvonne; Jansen, Manuela; Kluwig, David; Schmidt, Morna Friederike; Albuscheit, Nicole; von Felbert, Verena; , CTC-A Translation Group; Jockenhoevel, Stefan; Huth, Sebastian; Yazdi, Amir S.; et al. (Frontiers in Immunology, 2025)
Autoimmune bullous diseases (AIBDs) are acquired disorders characterized by autoantibodies targeting structural proteins of the skin and mucous membranes, resulting in blister formation. In pemphigus, pathogenic autoantibodies primarily directed against desmosomal adhesion proteins (desmoglein 1 and 3), disrupt epidermal cell-cell adhesion, leading to intraepidermal blister formation. In contrast, pemphigoid diseases are marked by subepidermal blistering due to autoantibodies against hemidesmosomal proteins, such as BP180 and BP230, located in the basement membrane zone. Diagnosis of AIBDs is based on clinical presentation, histolopathology, direct immunofluorescence, and serological analyses. Specific circulating autoantibodies can be identified using indirect immunofluorescence (IIF), which conventionally relies on animal-derived tissues, such as monkey esophagus, as substrates. This study aimed to develop a standardized in vitro diagnostic platform that eliminates the need for animal tissues. Human 3D skin models composed of dermal fibroblasts and epidermal keratinocytes were generated. Cryosections from these models were evaluated by IIF using sera from 34 patients diagnosed with either pemphigus vulgaris, pemphigus foliaceus, or bullous pemphigoid. As expected, sera from patients with pemphigus diseases produced the characteristic intercellular fluorescence pattern within the epidermis, while sera from pemphigoid patients exhibited staining along the basement membrane zone. These staining patterns precisely matched those obtained using monkey esophagus tissue. Notably, the 3D skin model demonstrated a significantly higher diagnostic sensitivity compared to the conventional monkey esophagus substrate. In summary, cryosections from human 3D skin models provide a sensitive and animal-free alternative for the serological diagnosis of AIBDs, accurately reproducing disease-specific immunofluorescence pattern.